Vanadium, sulfur, and iron valences in melt inclusions as a window into magmatic processes: A case study at Nyamuragira volcano, Africa. (1st April 2018) - Head, Elisabet; Lanzirotti, Antonio; Newville, Matthew; Sutton, Stephen
Abstract: This study describes microscale sulfur (S), vanadium (V), and iron (Fe) K-edge X-ray absorption near edge structure (µ-XANES) spectroscopy measurements on olivine-hosted melt inclusions (MI) preserved in tephras (1986 and 2006) and lavas (1938 and 1948) erupted from Nyamuragira volcano (D.R. Congo, Africa). The S, V, and Fe spectroscopic data are used to constrain the evolution of oxygen fugacity ( f O2 ) and sulfur speciation for the entrapped melts. Melt inclusions from lavas show evidence of post-entrapment crystallization and were thus reheated prior to µ-XANES analysis. The MI from tephra show no evidence of post-entrapment crystallization and were, therefore, not reheated. Sulfur, V, and Fe µ-XANES results from 1938, 1948, and 2006 eruptive materials are all similar within analytical uncertainty and provide similar average calculated melt f O2 's based on XANES oxybarometry. However, olivine-hosted MI from the 1986 tephras yield significantly different S, V, and Fe XANES spectra when compared to MI from the other eruptions, with disagreement between calculated f O2 's from the three valence state oxybarometers beyond the uncertainty of the calibration models. Their V µ-XANES spectra are also significantly more ordered and yield more reduced average V valence. The S µ-XANES spectra display a significantly more intense low-energy spectral resonance, which indicates differences in Fe-S bonding character, and greater variability in their measured sulfate content. These V and S spectroscopic features are best explained by crystallization of sub-micrometer magnetite and sulfide crystallites within the 1986 inclusions. The sensitivity of XANES spectroscopy to short-range order allows these crystallites to be recognized even though they are not easily detected by imaging analysis. This shows that V and S µ-XANES are potentially highly sensitive tools for identifying the presence of volumetrically minor amounts of spinel and sulfide within inclusions extracted from rapidly-cooled samples of tephra. Additionally, the observation that rehomogenized 1938 and 1948 inclusions from lava yield similar S, V, and Fe XANES spectra to the 2006 inclusions from tephra may be an encouraging indication that rehomogenization appears to have enabled the successful recovery of their pre-eruptive f O2, despite their complex post-eruptive histories.